Pengaruh Penerapan Mekanisme Good Corporate Governance Terhadap Indikasi Kecurangan Laporan Keuangan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Fadisa Talitha Sahda; Marsellisa Nindito; Hera Khairunnisa (LPPM Universitas Negeri Jakarta, 2025)
The purpose of this study is to examine how indicators of financial statement fraud in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the years 2021–2023 are impacted by the frequency of audit committee meetings, the percentage of independent board of commissioners, managerial ownership, institutional ownership, and gender diversity. Using a quantitative method and purposive sampling strategy, this research employs secondary data from company financial statements and annual reports. During the study period, 210 observation data points or 70 firms were acquired as samples. Using IBM SPSS Version 29 software, logistic regression analysis was the data analysis method employed in this research. The study's findings demonstrate that indicators of financial statement fraud are significantly impacted negatively by managerial and institutional ownership. In the meanwhile, signs of financial statement fraud are positively and negligibly impacted by the gender diversity and the proportion of the board of commissioners.